ON THE BOUNDEDNESS OF A CLASS OF THE FIRST ORDER LINEAR DIFFERENTIAL OPERATORS - Dumanyan, V.Zh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
In the present article the first order linear differential operators with unbounded coefficients are investigated. The boundedness of the operators under consideration was proved.